2016
DOI: 10.3892/mmr.2016.5616
|View full text |Cite
|
Sign up to set email alerts
|

Impact of quercetin-induced changes in drug-metabolizing enzyme and transporter expression on the pharmacokinetics of cyclosporine in rats

Abstract: The aim of the present study was to evaluate whether quercetin (Que) modulates the mRNA and protein expression levels of drug-metabolizing enzymes (DMEs) and drug transporters (DTs) in the small intestine and liver, and thus modifies the pharmacokinetic profile of cyclosporine (CsA) in rats. This two-part study evaluated the pharmacokinetic profiles of CsA in the presence or absence of Que (experiment I) and the involvement of DMEs and DTs (experiment II). In experiment I, 24 rats received single-dose CsA (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 68 publications
3
5
0
Order By: Relevance
“…Q3GA exerted a similar effect on the mRNA and protein expression levels. These results were consistent with our previous report about the regulation of DMEs and DTs by quercetin ( 28 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Q3GA exerted a similar effect on the mRNA and protein expression levels. These results were consistent with our previous report about the regulation of DMEs and DTs by quercetin ( 28 ).…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, the Q3GA co-administration exerted a marked effect on the pharmacokinetics of CsA. These results were consistent with our previous report that the oral administration of quercetin for 7 consecutive days reduced the bioavailability of CsA in rats ( 28 ). Yu et al ( 33 ) and Hsiu et al ( 37 ) reported the same results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Quercetin and Q3GA exhibited similar inhibitory effects on the protein and mRNA expression levels of UGT1A1 in the small intestine and the liver. This is consistent with our preliminary data and previously published studies ( 19 , 43 ). It has also been reported that quercetin inhibits glucuronidation of ethanol in human liver microsomes and in recombinant UGT1A1, UGT1A3, UGT 1A4, UGT1A6 and UGT1A9 enzymes ( 44 ).…”
Section: Discussionsupporting
confidence: 94%
“…Piperine treatment had shown to increase the oral bioavailability of various antibacterial drugs like pefloxacin (Madhukar et al, 2008), gatifloxacin (Patel et al, 2011), amoxicillin (Barve and Ruparel, 2015) and rifampicin (Singh et al, 2018). Quercetin, a flavonoid compound present in many plants and foods could also competitively inhibit the drug metabolizing enzyme CYP3A4 (Choi et al, 2011) and the members of MDR family MDR1, MRP2 and BCRP (Liu et al, 2016). Quercetin treatment had also shown to increase the bioavailability of ciprofloxacin in rat (Devi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%